Efektivitas Aktivitas dan Hasil Belajar IPS menggunakan Model Pair Checks - Machrulita Machrulita; Zainuddin Zainuddin; Siti Habsari Pratiwi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The right learning model can affect the student's learning outcomes. One model that can activate students in learning is pair checks. Pair checks emphasize activity, interaction, and insistence cooperation. The purpose of the study was to layout the improvement of student learning results on IPS learning by using pair checks models. The research paradigm is a class action. Research subjects of as many as 22 people of V grade students. Data collecting techniques use observation as well as data analysis using percentage. The results of the study showed that there was an increase in student learning outcomes. The results showed there was an increase in student learning results from cycle I to cycle II by 31.81%. This increase in learning outcomes is influenced by the students’ level of concentration and seriousness in following the IPS learning process better than ever and students are already used to feeling with those learning models as well. Thus, it can be concluded that the use of cooperative learning models of pair type checks is effective in improving the learning results of MIS Gp Meutia's V class students.